Pengaruh Motivasi dan Keaktifan terhadap Kemampuan Pemecahan Masalah Matematika di SD - Ifrah Muliyani E. Pulungan; Mufidah Hannum Nst; Almira Amir (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Problem-solving ability in mathematics is one of the essential competencies that elementary school students must master in order to face everyday life problems. However, the facts show that many students still experience difficulties when confronted with problems that are actually not too complex, due to their inability to formulate solution strategies. This is suspected to be caused by low learning motivation and minimal student engagement during the learning process. This study aims to examine the influence of learning motivation and student engagement on mathematical problem-solving ability in elementary school students. The approach used is quantitative with a correlational design. The research subjects include elementary school students selected through purposive sampling. Data collection was conducted through completion of learning motivation questionnaires, student engagement observation sheets, and problem-solving ability tests. The research results show that learning motivation has a positive and significant effect on problem-solving ability, while student engagement also makes a substantial contribution to the improvement of this ability.